OPTICAL FIBRES : Optimisation of an acoustically antiguiding structure for raising the stimulated Brillouin scattering threshold in optical fibres. (1st June 2016) - Khudyakov, M M; Likhachev, M E; Bubnov, M M; Lipatov, D S; Gur'yanov, A N; Temyanko, V; Nagel, J; Peyghambarian, N
Abstract: Optical fibres having a radially nonuniform acoustically antiguiding structure produced by codoping their core with alumina and germania have been fabricated and investigated. The influence of the shape of the antiguiding acoustic refractive index profile and fibre core diameter on the stimulated Brillouin scattering (SBS) threshold and spectrum in the fibres has been assessed. An increase in SBS threshold by 4.4 dB with respect to a germanosilicate fibre having the same mode field diameter has been demonstrated.